Carl Linnaeus the herpetologist: a review of his complete herpetological activity and legacy - Krecsák, László; Bauer, Aaron M. (Zootaxa, 2025)
We provide a complete overview of Linnaeus’s herpetological writings with specific focus on a review of his 89 herpetology related publications. A short biographical summary focused on key episodes of the life of Linnaeus is presented to facilitate the herpetologist reader to place the Linnaean publications in chronological order and to understand in which period of Linnaeus’s life as a scientist the particular work was issued, and thus comprehend the maturity of the different ideas in the particular publication(s). The development of his publications is presented from the initial idea Linnaeus had on a subject, through the elaboration of these subjects by his students and their publication as academic dissertations, to their revision and inclusion in the multi-volume publication ‘Amoenitates Academicae’. The Linnaean publications containing his 222 available Amphibia names are discussed. We present a short history of binominals linked to Amphibia, the key characters in his classification of the class, and further provide an overview of the sources of the existing Linnaean type material.